Comparison of capillary and arterial blood gas measurements in neonates. Issue 7 (July 1988) - McLain, B I; Evans, J; Dear, P R
Abstract : One hundred and fifty eight paired arterial and capillary blood samples were obtained from 41 sick preterm infants in their first week of life and the pH, and PCO2, and PO2 concentrations were measured. Half of the capillary samples were obtained from unwarmed heels and half from heels warmed to 40 degrees C. A potentially significant discrepancy (arbitrarily defined as 0.05 units for pH. 1 kPa for PCO2, and 3 kPa for PO2) was found in 19 (24%) of cases for pH, in 9 (11%) for PCO2 and in 21 (26%) for PO2. Warming the heel produced no significant improvement in results. We conclude that capillary blood provides satisfactory measurements of pH and PCO2 for all but the most critical purposes, but that the usefulness of capillary PO2 estimations is limited to the exclusion of hypoxia.